SAT0528 Molecular modifications induced by mud-bath therapy in patients with osteoarthritis. (15th June 2017) - Angioni, MM; Denotti, A; Pinna, S; Sanna, C; Floris, A; Piga, M; Loi, A; Cauli, A
Abstract : Background: Mud-bath therapy (MBT) is a non-pharmacological approach commonly used to treat osteoarthritis (OA). Several data indicate that MBT improve patient's symptoms (1), exerting a beneficial effect on pain and joint function, although the biological mechanisms involved in the therapeutic response are poorly defined. Objectives: This study aimed to find molecular changes (proteins and mRNA variations) in patients with OA after MBT treatment. Methods: The study included 39 patients whit primary diffuse osteoarthritis, assigned to receive a cycle of mud-bath therapy over a period of 2 weeks added to usual pharmacologic treatment. Whole blood and serum were collected before and after standard MBT treatment: for each time points two pools of patients sera were analyzed by the direct antigen-labeling technology (RayBio® Biotin Label-based Antibody Array, RayBiotech) obtaining a broad, panoramic view of protein expression. Using this semi-quantitative technique up to 1000 target proteins was simultaneously detected, making this approach ideally suited for proteomic studies. Again, pooled samples of mRNA were used to investigate genes expression and to perform the transcriptomic analysis using an high-resolution array design that contains >6.0 million distinct probes, covering coding and non-coding transcripts (GeneChip® HTA 2.0, Affymetrix). Results: At the end of mud-bath therapy, using first a semi-quantitative approach, we observed in both biological replicates increased levels (>1.5 fold change) of: inhibin beta A subunit (INHBA), activin A receptor type 2B (ACVR2B), angiopoietin-1 (ANGPT1), beta-2-microglobulin (B2M), growth differentiation factor 10 (BMP-3b/GDF10), C-X-C motif chemokine ligand 5 (CXCL5), fibroblast growth factor 2 (FGF2), fibroblast growth factor 12 (FGF12), oxidized low density lipoprotein receptor 1 (OLR1), matrix metallopeptidase 13 (MMP13). We observed that some increased proteins belongs to the same family or pathway: INHBA, ACVR2B and BMP-3b are members of TGF-Beta superfamily; CXCL5 and MMP13 participate into IL-17 signaling pathway; FGF2 and FGF12 are proteins of FGF family. We are currently performing the transcriptome analysis, and the next step will be to correlate detected proteins with mRNA levels considering also post-transcriptional or epigenetic modifications. Finally we will validate these findings with other quantitative techniques (like ELISA and RT-PCR). Conclusions: Our first proteomic and broad spectrum analysis suggest the implication of molecular pathways involved in a wide variety of cellular functions such as gene expression modulation, differentiation, angiogenesis, tissue repair, acute and chronic inflammatory response which may explain the beneficial effects of MBT observed in osteoarthritis. This "omic" approach (proteomic and transcriptomic), generated a huge amount of data that is currently under statistical and bioinformatic analysis. References: Forestier R, Desfour H, Tessier JM, et al. Spa therapy in the treatment of knee osteoarthritis: a large randomised multicentre trial. Ann Rheum Dis. 2010;69:660–5. Acknowledgements: Supported by Fondazione per la Ricerca Scientifica Termale (FORST) grant. Disclosure of Interest: None declared